Alternatif Kebijakan dalam Pembangunan Pertanian Berkelanjutan di Provinsi Papua - Indahyani, Rachmaeny; Maga, La (Analisis Kebijakan Pertanian, 2025)
One of the efforts to meet food needs is by increasing agricultural productivity. Efforts to increase agricultural productivity are not simple because, in practice, these efforts can negatively impact the environment. For example, efforts to increase agricultural productivity by using excessive use of chemical fertilizers will have a direct impact on the preservation of natural resources and the environment. Along with the development of technology in agriculture, various agricultural systems have been developed that can increase productivity while maintaining environmental sustainability. This study aims to formulate policy recommendations for sustainable agricultural development in Papua Province. Data analysis uses the Analytical Hierarchy Process method. The analysis uses a qualitative descriptive approach based on the results of interviews with respondents selected by purposive sampling method. Respondents came from the Papua Provincial Government agencies, namely BAPPEDA, the Agriculture Service, and the Forestry and Environment Service, one respondent each. Based on the analysis results, the main factor constraining sustainable agricultural development in Papua Province is limited human resources. The local wisdom of the Papuan people is an opportunity for sustainable agricultural development in Papua Province. Based on the existing constraints and opportunities, an alternative policy for sustainable agriculture development in Papua Province is to apply the agroforestry farming. For this reason, it is necessary to increase the knowledge and skills of local farmers. The central and regional governments are advised to formulate policies to improve the living standards of local farmers who still apply organic farming.